Football injuries during the 2014 FIFA World Cup - Junge, A.; Dvorák, J. (British Journal of Sports Medicine, 2015)
Background: FIFA has surveyed match injuries in its tournaments since 1998. Aim: To analyse the incidence and characteristics of match injuries incurred during the 2014 FIFA World Cup in comparison to previous FIFA World Cups. Methods: The chief physicians of the participating teams reported all newly incurred injuries of their players after the match on a standardised report form. 124 (97%) forms were returned. Results: A total of 104 injuries were reported, equivalent to an incidence of 1.68 injuries per match (95% CI 1.36 to 2.00). 64 (63.4%) injuries were caused by contact with another player. Thigh (26; 25%) and head (19; 18%) were the most frequently injured body parts. The most frequent diagnosis was thigh strain (n=18). Five concussions and three fractures to the head were reported. While most thigh strains (15/17; 88.2%) occurred without contact, almost all head injuries (18/19; 94.7%) were caused by contact. 0.97 injuries per match (95% CI 0.72 to 1.22) were expected to result in absence from training or match. Eight injuries were classified as severe. The incidence of match injuries in the 2014 FIFA World Cup was significantly lower than the average of the four preceding FIFA World Cups, both for all injuries (2.34; 95% CI 2.15 to 2.53) and time-loss injuries (1.51; 95% CI 1.37 to 1.65). Conclusions: The overall incidence of injury during the FIFA World Cups decreased from 2002 to 2014 by 37%. A detailed analysis of the injury mechanism is recommended to further improve prevention strategies.